The Process of Advance Care Planning in HCT Candidates and Proxies: Self-Efficacy, Locus of Control, and Anxiety Levels. (November 2014) - Duckworth, Katharine E.; Forti, Allison M.; Russell, Gregory B.; Naik, Seema; Hurd, David; McQuellon, Richard P.
The purpose of this study was to examine the relationship between hematopoietic cell transplant candidate and proxy advance care planning (ACP) behavior and attitudes. A total of 49 candidates and 44 proxies completed the Advance Directive Attitudes Survey, Multidimensional Health Locus of Control Scale, Family Decision Making Self-Efficacy Scale, and the State-Trait Anxiety Inventory. In all, 45% of candidates reported completing an advance directive (AD), while only 26% had ADs on file; 80% of candidates discussed ACP wishes with their loved ones and 15% discussed ACP wishes with their medical team. The AD completers were significantly (1) older, (2) more positive about ADs, and (3) were less likely to believe that health events happen by chance. Discrepancies between reported ACP behavior and communication with health care practitioners have implications for end-of-life care.